Current Issues and Perspectives in Patients with Possible Sepsis at Emergency Departments - Ioannis Alexandros Charitos; Skender Topi; Francesca Castellaneta; Donato D'Agostino (MDPI AG, 2019)
In the area of Emergency Room (ER), many patients present criteria compatible with a SIRS, but only some of them have an associated infection. The new definition of sepsis by the European Society of Intensive Care Medicine and the Society of Critical Care Medicine (2016), revolutionizes precedent criteria, overcoming the concept of SIRS and clearly distinguishing the infection with the patient’s physiological response from the symptoms of sepsis. Another fundamental change concerns the recognition method: The use of SOFA (Sequential-Sepsis Related-Organ Failure Assessment Score) as reference score for organ damage assessment. Also, the use of the qSOFA is based on the use of three objective parameters: Altered level of consciousness (GCS <15 or AVPU), systolic blood pressure ≤ 100 mmHg, and respiratory rate ≥ 22/min. If patients have at least two of these altered parameters in association with an infection, then there is the suspicion of sepsis. In these patients the risk of death is higher, and it is necessary to implement the appropriate management protocols, indeed the hospital mortality rate of these patients exceeds 40%. Patients with septic shock can be identified by the association of the clinical symptoms of sepsis with persistent hypotension, which requires vasopressors to maintain a MAP of 65 mmHg, and serum lactate levels >18 mg/dL in despite of an adequate volume resuscitation. Then, patient first management is mainly based on: (1) Recognition of the potentially septic patient (sepsis protocol-qSOFA); (2) Laboratory investigations; (3) Empirical antibiotic therapy in patients with sepsis and septic shock. With this in mind, the authors discuss the most important aspects of the sepsis in both adults and infants, and also consider the possible treatment according current guidelines. In addition, the possible role of some nutraceuticals as supportive therapy in septic patient is also discussed.